1998
DOI: 10.1111/j.1471-0528.1998.tb10185.x
|View full text |Cite
|
Sign up to set email alerts
|

Flexible outpatient hysteroscopy without anaesthesia: a safe, successful and well tolerated procedure

Abstract: The objective of this study was to assess the feasibility and tolerance of diagnostic outpatient flexible hysteroscopy without anaesthesia. Records from 554 consecutive patients were analysed retrospectively. Success rate, reasons for failure, adverse reactions and level of pain were the main outcome measures. Hysteroscopy was successful in 90.5% of patients and well tolerated in 93.3%; 5.4% experienced moderate to severe pain. Inability to negotiate the cervical canal accounted for 47% of failed procedures an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
2
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 17 publications
4
42
2
2
Order By: Relevance
“…39 We found a hysteroscopic diagnosis of polyps in 33.2% of asymptomatic postmenopausal ER-positive women, and higher than that reported in 2009 by Dreisler et al, 30 who found polyps in 13% (22/169) of asymptomatic postmenopausal 19,35,40,41 found a much lower incidence of endometrial polyps, and we believe that this is so because they did not perform hysteroscopy on patients with an endometrial thickness of less than 4 mm and their patients were younger and less obese than those in our study. In 35 of 40 (87.5%) hysteroscopic diagnoses of endometrial polyps in our postmenopausal women, diagnosis was histologically confirmed, representing an acceptable rate of falsepositive findings on hysteroscopic screening.…”
Section: Discussionmentioning
confidence: 48%
“…39 We found a hysteroscopic diagnosis of polyps in 33.2% of asymptomatic postmenopausal ER-positive women, and higher than that reported in 2009 by Dreisler et al, 30 who found polyps in 13% (22/169) of asymptomatic postmenopausal 19,35,40,41 found a much lower incidence of endometrial polyps, and we believe that this is so because they did not perform hysteroscopy on patients with an endometrial thickness of less than 4 mm and their patients were younger and less obese than those in our study. In 35 of 40 (87.5%) hysteroscopic diagnoses of endometrial polyps in our postmenopausal women, diagnosis was histologically confirmed, representing an acceptable rate of falsepositive findings on hysteroscopic screening.…”
Section: Discussionmentioning
confidence: 48%
“…The use of local anaesthesia, with intracervical or paracervical block, in hysteroscopy has been studied extensively, with little evidence of reduction in pain. Our standard procedure using no anaesthesia has been shown to be successful and well tolerated 10,11 , with a mean pain score of 2.3 in these studies. This level has increased slightly in the present study, possibly as a result of the greater proportion of postmenopausal women investigated, with a mean pain score of 3.6 for hysteroscopy and a lower score of 2.5 for saline infusion hysterosonography.…”
Section: Discussionmentioning
confidence: 72%
“…The transvaginal probe and catheter were then removed and a visual analogue pain score was performed. The speculum was replaced and a 3.1-mm flexible hysteroscope (KeyMed Olympus, UK) was inserted, observing the uterine cavity on a high-resolution colour monitor using a single-chip camera 10,11 . Saline was used as the distension medium, with both tubal ostia being noted and the endometrial appearances documented.…”
Section: Methodsmentioning
confidence: 99%
“…Kremer et al 22 and Nagele et al 24 found a higher incidence of polyps and fibroids. La Sala et al 23 found a similar incidence of polyps and fibroids in patients with postmenopausal bleeding.…”
Section: Discussionmentioning
confidence: 95%